Gambaran Self Disclosure Remaja yang Mengalami Broken Home Pengaruh Persepsi Peringatan Bergambar pada Kemasan Rokok Terhadap Minat Beli Konsumen Remaja Akhir di Desa Karang Dima Sumbawa Besar - Ivon Arisanti; Iswanto (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2021)
The rapid development of the cigarette industry in Indonesia has caused the number of cigarette consumers to increase. The government issued Minister of Health Regulation No. 28 of 2013, requiring every cigarette manufacturer to include a pictorial warning on every cigarette package whose impact is expected to increase smokers' knowledge and reduce the number of smokers. This is strongly influenced by perceptions and buying interests. This study aims to determine the effect of the perception of pictorial warnings on the buying interests of late adolescent consumers. One of the areas that is the object of research is Karang Dima Village, located in Sumbawa Regency, West Nusa Tenggara Province, Indonesia. Data analysis in this study uses a descriptive quantitative approach, where the sampling technique uses the analysis of the solving formula. The sample in this study amounted to 72 adolescents in the village of Karang Dima. The data were collected using two scales of research instruments: the perception scale and the buying interest scale.The results of this study indicate that the hypothesis (Ho), which states